The Ancient Pottery of Israel and Its Neighbors from the Iron Age through the Hellenistic Period - Gitin, Seymour (Journal of Hellenistic Pottery and Material Culture, 2017)
These two volumes, published in 2015 by the Israel Exploration Society, the W.F. Albright Institute of Archaeological Research, the Israel Antiquities Authority and the American Schools of Oriental Research, offer a comprehensive corpus of ceramic forms and their typological development organized according to period, geographical region, and cultural tradition.